Diagnostic accuracy of repeat placental growth factor measurements in women with suspected preeclampsia: A case series study. (29th February 2020) - Duhig, Kate E.; Webster, Louise M.; Sharp, Andrew; Gill, Carolyn; Seed, Paul T.; Shennan, Andrew H.; Myers, Jenny E.; Chappell, Lucy C.
Abstract: Introduction: Preeclampsia affects about 3% of singleton pregnancies and is characterized by placental dysfunction. It is associated with significant maternal and perinatal morbidity and mortality. The diagnosis of preeclampsia remains a challenge, and the clinical course can develop for weeks before a diagnosis is confirmed. National guidelines have approved placental growth factor (PlGF) testing to rule out suspected preeclampsia, but the utility of repeated PlGF measurement is unknown. The aim of this case series analysis was to evaluate the test performance of repeated PlGF sampling in women presenting with suspected preeclampsia, and to describe relevant clinical outcomes. Material and methods: Women who presented to maternity services with suspected preeclampsia between 20 +0 and 36 +6 weeks' gestation who underwent repeat PlGF sampling with a minimum test interval of 7 days were assessed. The outcomes were delivery for preeclampsia within 14 days of sampling, the proportion changing PlGF categories, and time to delivery. Results: In total, 289 women with suspected preeclampsia undergoing repeat PlGF sampling were included. PlGF <100 pg/mL had a high sensitivity (87.5%, 95% confidence interval [CI] 67.6%‐97.3%) and a negative predictive value (97.7%, 95% CI 93.5%‐99.5%) at the initial test (receiver operating characteristic [ROC] area 0.79, 95% CI 0.68‐0.89). Similar test performance was seen for PlGF <100 pg/mL when undertaken as a repeat test (sensitivity 90.7%, 95% CI 85.2%‐95.9%, negative predictive value 92.2%, 95% CI 85.3‐96.6%). Overall, 25.6% of women changed PlGF category between the first and second PlGF tests. For each PlGF category, determination of time to delivery was similar for first and second tests. Conclusions: Repeat PlGF measurement demonstrates high negative predictive value for determining preeclampsia requiring delivery in 14 days. Repeat testing may be clinically useful to risk stratify women with ongoing symptoms of disease. Confirmation of the impact of these findings is required in further studies.